A Case of Stevens–Johnson Syndrome Triggered by Methicillin‐Resistant Staphylococcus aureus Infection During Pembrolizumab Treatment for Lung Squamous Cell Carcinoma - Yusuke Irie; Kazutoshi Isobe; Ryogo Ohashi; Kensuke Namba; Misa Iwayanagi; Hiromasa Sakurai; Daiki Sakai; Kenta Takashima; Yu Murakami; Kaichi Kaneko; Nobuharu Mitsuyama; Hiroki Wakabayashi; et al. (Respirology Case Reports, 2025)
ABSTRACT Pembrolizumab can cause extremely serious skin disorders with high mortality rates, such as Stevens–Johnson syndrome (SJS), with most cases occurring early after immune checkpoint inhibitor treatment. This report describes a patient that developed SJS triggered by methicillin‐susceptible Staphylococcus aureus (MSSA) infection 8 months into pembrolizumab treatment for lung squamous cell carcinoma. A 74‐year‐old male developed fever, oral mucosal damage, oedematous erythema with erosions predominantly in the trunk and renal dysfunction 8 months after starting pembrolizumab monotherapy for the postoperative recurrence of lung squamous cell carcinoma. SJS was diagnosed and the patient was hospitalised. Cultures of purulent exudates from the facial skin and sputum revealed MSSA. The skin and mucosa findings did not improve despite steroid pulse therapy, but gradual improvements were seen after treatment with ampicillin–sulbactam, vancomycin and four sessions of plasma exchange therapy.